2004
DOI: 10.1111/j.1365-4632.2004.01842.x
|View full text |Cite
|
Sign up to set email alerts
|

Case of leukoderma punctata after topical PUVA treatment

Abstract: An 11‐year‐old Korean girl presented with a 2‐year history of asymptomatic multiple punctiform, hypopigmented and achromic spots predominantly on the outer aspect of her right forearm. She had been treated for segmental vitiligo on her right forearm with topical PUVA six times a week for 4 years at a local clinic. The lesions were very distinct, round hypopigmented macules 1–2 mm in diameter, predominantly in nonfollicular distribution (Fig. 1). Not only the site where topical psolaren had been applied but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…This hypopigmentation has also been described in relation to other phototherapeutic modalities used for the treatment of vitiligo and psoriasis 1,4 . The histopathologic features of punctate leucoderma, which consists of a decrease in the number of functional melanocytes and a patch loss of melanin pigment in basal keratinocytes, indicate that phototoxicity‐induced damage to melanocytes is the most likely pathogenesis 3–5 . The histopathologic findings of our patient show the characteristic features of conventional punctate leucoderma, so hypopigmentation after 1,064‐nm QSNY with low fluence may originate from laser‐induced photodamage to melanocytes.…”
supporting
confidence: 75%
“…This hypopigmentation has also been described in relation to other phototherapeutic modalities used for the treatment of vitiligo and psoriasis 1,4 . The histopathologic features of punctate leucoderma, which consists of a decrease in the number of functional melanocytes and a patch loss of melanin pigment in basal keratinocytes, indicate that phototoxicity‐induced damage to melanocytes is the most likely pathogenesis 3–5 . The histopathologic findings of our patient show the characteristic features of conventional punctate leucoderma, so hypopigmentation after 1,064‐nm QSNY with low fluence may originate from laser‐induced photodamage to melanocytes.…”
supporting
confidence: 75%
“…Most of the cases were females. Recently, it has been reported after topical PUVA treatment for segmental vitiligo by Park et al 6 The typical skin lesions described are multiple discrete well-defined macules of size varying from 0.5 to 1.5 mm, most commonly located on the upper and lower extremities. Recently, it has been reported after topical PUVA treatment for segmental vitiligo by Park et al 6 The typical skin lesions described are multiple discrete well-defined macules of size varying from 0.5 to 1.5 mm, most commonly located on the upper and lower extremities.…”
Section: Confetti-like Hypopigmentation: a Rare Complication Of Commomentioning
confidence: 99%
“…1,2 Leucoderma punctatum, a confetti-like hypopigmentation, as a distinct entity was first described by Falabela et al 3 A 21-year-old woman presented with multiple asymptomatic, punctiform, achromic spots of 1-month duration, distributed predominantly on extensor aspect of extremities. Recently, it has been reported after topical PUVA treatment for segmental vitiligo by Park et al 6 The typical skin lesions described are multiple discrete well-defined macules of size varying from 0.5 to 1.5 mm, most commonly located on the upper and lower extremities. Before starting PUVA treatment she was given 8 months' treatment of narrowband ultraviolet B (NBUVB), during which no similar lesion was observed.…”
mentioning
confidence: 99%
“…Leukoderma punctatum represents a clinical condition presenting as confetti‐like hypopigmented macules described most commonly in women being treated with 8‐methoxypsoralen and sunlight as a UV source for vitiligo but also has been reported with light chamber UV‐A and topical PUVA 13–15 . Park et al reported four cases of generalized leukoderma punctatum after UV‐B phototherapy for psoriasis, while Bhatnagar et al reported a single case of a vitiligo patient who had both UV‐B and PUVA therapy that developed the leukoderma punctatum after the PUVA 16,17 .…”
Section: Discussionmentioning
confidence: 99%